Variability of dinoflagellates and their associated toxins in relation with environmental drivers in Ambon Bay, eastern Indonesia. (January 2020) - Likumahua, Sem; de Boer, M. Karin; Krock, Bernd; Hehakaya, Salomy; Imu, La; Müller, Annegret; Max, Thomas; Buma, Anita G.J.
Abstract: The aim of the present work was to unravel which environmental drivers govern the dynamics of toxic dinoflagellate abundance as well as their associated paralytic shellfish toxins (PSTs), diarrhetic shellfish toxins (DSTs) and pectenotoxin-2 (PTX2) in Ambon Bay, Eastern Indonesia. Weather, biological and physicochemical parameters were investigated weekly over a 7-month period. Both PSTs and PTX2 were detected at low levels, yet they persisted throughout the research. Meanwhile, DSTs were absent. A strong correlation was found between total particulate PST and Gymnodinium catenatum cell abundance, implying that this species was the main producer of this toxin. PTX2 was positively correlated with Dinophysis miles cell abundance. Vertical mixing, tidal elevation and irradiance attenuation were the main environmental factors that regulated both toxins and cell abundances, while nutrients showed only weak correlations. The present study indicates that dinoflagellate toxins form a potential environmental, economic and health risk in this Eastern Indonesian bay. Highlights: Persistent occurrences of toxic dinoflagellate species and their associated toxin in Ambon Bay. Paralytic shellfish toxin levels strongly correlated with Gymnodinium catenatum cell abundances. The first record of Dinophysis miles correlating with Pectenotoxin-2 (PTX2) in natural samples. Vertical mixing, tidal elevation and irradiance attenuation regulated both toxins and cell abundances. Dinoflagellate toxins form a potential environmental, economic and health risk in this semi-enclosed bay.